2020
DOI: 10.1016/j.ebiom.2020.102890
|View full text |Cite
|
Sign up to set email alerts
|

Lack of antibody-mediated cross-protection between SARS-CoV-2 and SARS-CoV infections

Abstract: Background The novel coronavirus (SARS-CoV-2) shares approximately 80% whole genome sequence identity and 66% spike (S) protein identity with that of SARS-CoV. The cross-neutralization between these viruses is currently not well-defined. Methods Here, by using the live SARS-CoV-2 virus infection assay as well as HIV-1 based pseudotyped-virus carrying the spike (S) gene of the SARS-CoV-2 (ppSARS-2) and SARS-CoV (ppSARS), we examined whether infections with SARS-CoV and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Furthermore, cross-neutralization of SARS-CoV-2 can be induced by sera from convalescent SARS-CoV patients, which is likely due to high homology between these two viruses, though it seems to be serum dependent. 56 , 57 Thus, our results indicate an absence of cross-neutralization between SARS-CoV-2 and other endemic human coronaviruses, suggesting that nAbs or other non-nAbs 6 generated by previous infections with other coronaviruses do not protect against SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, cross-neutralization of SARS-CoV-2 can be induced by sera from convalescent SARS-CoV patients, which is likely due to high homology between these two viruses, though it seems to be serum dependent. 56 , 57 Thus, our results indicate an absence of cross-neutralization between SARS-CoV-2 and other endemic human coronaviruses, suggesting that nAbs or other non-nAbs 6 generated by previous infections with other coronaviruses do not protect against SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 66%
“…Theoretically, the native HIV-1 Env trimer present on the surface of intact virions is thought to be a most ideal immunogen (60), as most of the neutralizing antibodies thus far described could recognize and bind to the prefusion form of trimeric HIV-1 Env, although it is with great difficulty that such neutralizing antibodies against this glycan-covered, sequence-variable native form are induced (36). For SARS-CoV-2, different lines of research have shown that convalescent sera from SARS-CoV and SARS-CoV-2 patients showed no or limited crossneutralization activity against these two viruses by pseudotyped and authentic viral infection assays, despite significant crossreactivity in binding to the S glycoproteins of both viruses (9,(79)(80)(81). Similar results were also observed in infected or immunized animals (48,79,81).…”
Section: Insights Into the Design And Development Of S Protein-basedmentioning
confidence: 99%
“…For SARS-CoV-2, different lines of research have shown that convalescent sera from SARS-CoV and SARS-CoV-2 patients showed no or limited crossneutralization activity against these two viruses by pseudotyped and authentic viral infection assays, despite significant crossreactivity in binding to the S glycoproteins of both viruses (9,(79)(80)(81). Similar results were also observed in infected or immunized animals (48,79,81). Together with the finding that although the SARS-CoV-2 S protein shares a high degree of amino acid sequence identity with that of SARS-CoV (~76% overall), the RBM is less conserved (~47% identity) than any other functional region or domain (82), it can thus been surmised that the RBM has the most immunodominant neutralizing epitope(s) of the whole S protein, capable of readily eliciting strong neutralizing antibody responses.…”
Section: Insights Into the Design And Development Of S Protein-basedmentioning
confidence: 99%
“…The experiment was conducted in a BSL-3 laboratory, as previously reported 2528 . Briefly, the sera were 2-fold serially diluted using 2% FBS-DMEM and mixed with the same volume of live SARS-CoV-2 (C-Tan-nCoV strain 04, 100TCID50), the mixtures were incubated at 37 °C for 1 h, following which they were added to the seeded Vero cells.…”
Section: Methodsmentioning
confidence: 99%